Trust and retirement preparedness: Evidence from Singapore - KOH, Benedict S. K. (Institutional Knowledge at Singapore Management University, 2021)
Trust is an essential component of any financial system, and distrust can undermine savings and economic growth. Our study draws on the Singapore Life Panel to assess how trust ties to older respondents’ (1) pension plan participation and withdrawals; (2) life, health, and long-term care insurance holdings; and (3) stock market engagement. We show that the widely-used ‘trust in people’ question is uncorrelated with household behaviours related to retirement preparedness. Instead, trust in private and public financial representatives is positively associated with pension savings, investments, and insurance holdings. Financial literacy also plays an important and consistent role in retirement decision-making.